Association between inflammatory response and outcome after subarachnoid haemorrhage. (22nd October 2020) - Bjerkne Wenneberg, Sandra; Odenstedt Hergès, Helena; Svedin, Pernilla; Mallard, Carina; Karlsson, Thomas; Adiels, Martin; Naredi, Silvana; Block, Linda
Abstract : Objectives: Recent reports suggest an association between the inflammatory response after aneurysmal subarachnoid haemorrhage (aSAH) and patients' outcome. The primary aim of this study was to identify a potential association between the inflammatory response after aSAH and 1‐year outcome. The secondary aim was to investigate whether the inflammatory response after aSAH could predict the development of delayed cerebral ischaemia (DCI). Materials and methods: This prospective observational pilot study included patients with an aSAH admitted to Sahlgrenska University Hospital, Gothenburg, Sweden, between May 2015 and October 2016. The patients were stratified according to the extended Glasgow Outcome Scale (GOSE) as having an unfavourable (score: 1–4) or favourable outcome (score: 5–8). Furthermore, patients were stratified depending on development of DCI or not. Patient data and blood samples were collected and analysed at admission and after 10 days. Results: Elevated serum concentrations of inflammatory markers such as tumour necrosis factor‐α and interleukin (IL)‐6, IL‐1Ra, C‐reactive protein and intercellular adhesion molecule‐1 were detected in patients with unfavourable outcome. When adjustments for Glasgow coma scale were made, only IL‐1Ra remained significantly associated with poor outcome ( p = 0.012). The inflammatory response after aSAH was not predictive of the development of DCI. Conclusion: Elevated serum concentrations of inflammatory markers were associated with poor neurological outcome 1‐year after aSAH. However, inflammatory markers are affected by many clinical events, and when adjustments were made, only IL‐1Ra remained significantly associated with poor outcome. The robustness of these results needs to be tested in a larger trial.